2002
DOI: 10.1016/s0047-2352(01)00131-3
|View full text |Cite
|
Sign up to set email alerts
|

Risk of multiple-offender rape–murder varies with female age

Abstract: Previous work inspired by an evolutionary perspective found that reproductive-age females are at special risk for single-offender rape and rape -murder, relative to non-reproductive-age females. The current research replicated and extended these findings to multiple-offender rape -murder. The author obtained access to a national database of homicides and selected for analysis cases in which a female was (a) raped and murdered by at least two males previously unknown to her, or (b) murdered in the context of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…However, the majority of offenders in the present sample were strangers. Shackleford (2002aShackleford ( , 2002b found that young women are the most vulnerable age group for rape-murder and also for multiple offender rape-murder, and discuss an evolutionary psychology perspective, offering the explanation that rapists target young women because of their capacity to bear offspring. A further explanation might be that young women are available through increased opportunity, that is, that compared with older women, young women are more likely to be in vulnerable positions and to be around young men (Mustaine 1997).…”
Section: Characteristicsmentioning
confidence: 99%
“…However, the majority of offenders in the present sample were strangers. Shackleford (2002aShackleford ( , 2002b found that young women are the most vulnerable age group for rape-murder and also for multiple offender rape-murder, and discuss an evolutionary psychology perspective, offering the explanation that rapists target young women because of their capacity to bear offspring. A further explanation might be that young women are available through increased opportunity, that is, that compared with older women, young women are more likely to be in vulnerable positions and to be around young men (Mustaine 1997).…”
Section: Characteristicsmentioning
confidence: 99%
“…From an evolutionary psychological perspective that strictly discounts proximal motives, such a strategy is maladaptive in that it directly countermands the adaptive mechanisms involved in rape. However, the adaptiveness of rape-murder becomes clear in light of the current model, which holds that the risk of detection from committing the crime of rape outweighs the fitness advantages of impregnating a rape victim (see Shackelford, 2002a, 2002b). The second is second-person (or higher) exposure, witness-centered homicide : As a consequence of committing some offense, other individual(s) who are not directly victimized in the original offense are exposed (or believed to be exposed) to the transgression and to the identity of the perpetrator.…”
Section: Co-optation Of Mechanisms Motivating Conspecific Killing By mentioning
confidence: 97%